A review on technical improvements, economic feasibility and world scenario of solar water heating system. (February 2017) - Gautam, Abhishek; Chamoli, Sunil; Kumar, Alok; Singh, Satyendra
Abstract: The solar water heating system (SWHS) is one of the most common application of solar energy utilization system. The usage of solar water heating system is not commonly employed throughout the globe, due to its high initial cost. The advancement in SWHS will lead to be beneficial over conventional system over the long span of time. The eco-friendly nature of such system promotes these systems to be used frequently in both domestic and industrial heating. The investigators throughout the globe focusing on technical advancement as well as economic feasibility of SWHS. The present study focused on to report such studies, which demonstrates the economic feasibility of SWHS in the long run. The payback period of SWHS varies from one origin to other as it depends on numerous factors like price of fossil fuels, rate of subsidy, solar insolation etc. Initially the paper reported the basic components of SWHS, and their advancements, further the global scenario of SWHS is discussed, followed by the studies reported on a techno economic analysis of SWHS, which shows that the economic feasibility is equally important as technical feasibility for its implementation. The last section inculcates the recent studies on the technical advancement of SWHS and the future research trends of SWHS were discussed.